Climate change and nephrology. Issue 1 (2nd September 2021) - Sasai, Fumihiko; Roncal-Jimenez, Carlos; Rogers, Keegan; Sato, Yuka; Brown, Jared M; Glaser, Jason; Garcia, Gabriela; Sanchez-Lozada, Laura Gabriela; Rodriguez-Iturbe, Bernardo; Dawson, Jaime Butler; Sorensen, Cecilia; Hernando, Ana Andres; et al.
Abstract: Climate change should be of special concern for the nephrologist, as the kidney has a critical role in protecting the host from dehydration, but it is also a favorite target of heat stress and dehydration. Here we discuss how rising temperatures and extreme heat events may affect the kidney. The most severe presentation of heat stress is heat stroke, which can result in severe electrolyte disturbance and both acute and chronic kidney disease (CKD). However, lesser levels of heat stress also have multiple effects, including exacerbating kidney disease and precipitating cardiovascular events in subjects with established kidney disease. Heat stress can also increase the risk for kidney stones, cause multiple electrolyte abnormalities and induce both acute and chronic kidney disease. Recently there have been multiple epidemics of CKD of uncertain etiology in various regions of the world, including Mesoamerica, Sri Lanka, India and Thailand. There is increasing evidence that climate change and heat stress may play a contributory role in these conditions, although other causes, including toxins, could also be involved. As climate change worsens, the nephrologist should prepare for an increase in diseases associated with heat stress and dehydration.